Building Internal Coaching Capacity: Key Ingredients for Developing Internal Champions in the Workplace - Mehdi Ebrahimi (Journal of Development and Administrative Studies, 2024)
An ongoing gap in the literature highlights the need to explore and address the essential elements required to build internal coaching capacity and develop effective internal coaches within organisations. This paper contributes to addressing this gap by exploring the essential ingredients critical for building internal coaching capacity. The main objective of this paper is to enhance our understanding of the factors that contribute to building internal coaching capacity, thereby supporting the design and implementation of effective internal coaching programs within organisations. First, an online survey was used to collect quantitative data, offering a general overview of coaching activities across Australia's rail organisations. This was followed by a qualitative phase, which involved semi-structured interviews with participants from two major rail organisations. Results from both the quantitative and qualitative phases indicate that organisations widely utilise both internal and external coaching, with internal coaching primarily occurring in an informal form. The qualitative findings relevant to the objective of this study suggest that (1) formalising internal coaching practices and ensuring accessibility across organisational hierarchies, (2) maintaining synergies between internal and external coaching activities while concurrently engaging in extensive internal coach training, (3) securing leadership commitment and support from upper management, and (4) cultivating a learning culture to support coaching can be considered among key components in building internal coaching capacity, and driving more effective coaching programs within organisations.